KECERNAAN NUTRIEN DAN PARAMETER RUMEN PAKAN KONSENTRAT YANG MENGANDUNG TEPUNG DAUN KERSEN SEBAGAI PENGGANTI JAGUNG SECARA IN VITRO (In vitro nutrient digestibility and rumen parameter of concentrate feed base chery leaf meal as corn substitution) - Kristina Jhena; Markus M. Kleden; Imanuel Benu (Universitas Nusa Cendana, 2020)
The present study aimed to determine the effect of concentrate base cherry leaves (Muntingia calabura L) substituting corn meal on in vitro nutrient digestibility and rumen parameter. This study was conducted in the laboratory of feed chemistry Faculty of animals Husbandry University of Nusa Cendana. The experiment was subjected to a completely randomized design (CRD) with 4 treatments and 3 replications. The tested treatments were: MC0 = concentrate containing 100% corn meal without cherry leaf meal; MC20 = concentrate containing 80% corn meal + 20% cherry leaf meal; MC40 = concentrate containing 60% corn meal + 40% cherry leaf meal; MC60 = concentrate containing 40% corn meal + 60% cherry leaf meal. The result showed that corn replacement by muntingia calabura leaves meal in concentrate feed decrease nutrient digestibility. In contrary the rumen parameter had increase value. Statistical analysis showed that the the parameter measured was very high depend on the Muntingia leaves meal utilization. As a conclusion that Muntingia calabura leaves can be used as corn substitution up to 20%.